2016
DOI: 10.1352/1944-7558-121.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Reading Skills in Down Syndrome: An Examination of Orthographic Knowledge

Abstract: The primary purpose of the present study was to examine orthographic knowledge in a sample of individuals with Down syndrome (DS) in comparison to typically developing (TD) children matched on word identification ability. Phonological recoding was also compared across groups. A secondary purpose of the study was to estimate literacy rates in DS using parent reports. Results of the parent study revealed that most individuals with DS over the age of 5 years can read words. Results of the child study revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 135 publications
0
4
0
1
Order By: Relevance
“…Six of these studies [47,48,49,50,51,53] found an impairment in non-word reading compared to reading level-matched controls but four [44,45,46,52] did not. Only a few studies selected groups based on measures other than word reading.…”
Section: Resultsmentioning
confidence: 99%
“…Six of these studies [47,48,49,50,51,53] found an impairment in non-word reading compared to reading level-matched controls but four [44,45,46,52] did not. Only a few studies selected groups based on measures other than word reading.…”
Section: Resultsmentioning
confidence: 99%
“…Más específicamente, con la enseñanza de la lectura temprana se pretende que el niño con SD practique lo antes posible de un tipo de metodología motivante que por un lado aproveche los puntos fuertes a nivel cognitivo del SD ya que sus logros suelen ser mejores de lo esperado dadas sus dificultades de aprendizaje (bajo CI), retraso en el habla, lenguaje, memoria de trabajo y capacidades motrices (Robles, 2010). Loveall & Conners (2016) relacionan esta fortaleza en la identificación de palabras en niños con SD con el desarrollo en el conocimiento ortográfico específico a las palabras diferenciándolo. Para esos autores, el énfasis en este conocimiento ortográfico específico a la palabra puede ser el producto de programas de enseñanza de la lectura centrados en el reconocimiento de la palabra total y/o de la estrategia adoptada por los niños con SD ante sus dificultades con la recodificación fonológica.…”
Section: Discussionunclassified
“…Both are norm‐referenced, standardised assessments with adequate reliability and validity that have previously been used successfully with participants with ID (e.g. Loveall and Conners, 2016).…”
Section: Methodsmentioning
confidence: 99%